The Auto/biographical Nature of Ukrainian Women’s Literature on the War in Donbas - Gaidash, Anna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2024)
In the close reading of Natal’ya Vorozhbit’s drama Bad Roads (2017), Yevgeniya Podobna’s book of stories and memoirs titled Girls Cutting Their Locks (2018), and Tamara Duda’s novel Daughter (2019), the author of the article examines the relations between subject and object of the Donbas war texts in the framework of their creation, auto/biographic nature, gender optics, and therapeutic effect. The goal of the study is to analyze how auto/biographical narratives employ actualization of life, leading to the fictionalization of drama and prose texts, which results in heterobiography or synthesis of auto/biographical narratives with heterobiographies. Mostly processed by professional writers, the documentary accounts of military experience of women characters convey the evidence of Zeitgeist, which forms a unique writing in modern war literature. The paper discusses the perspective of women, forms of undermining patriarchy, and rhetoric of “national autobiography” along with self-consciousness and self-reflexivity as markers of auto/biographical texts of Ukrainian women writers of the period in the selected texts.